Brønsted acid-catalysed enantioselective construction of axially chiral arylquinazolinones - Yong-Bin Wang (Nature Portfolio, 2017)
Axially chiral arylquinazolinones are structural motifs in several natural products and can also act as chiral ligands. Here, the authors show a chiral phosphoric acid-catalysed strategy to access enantiomerically pure arylquinazolinones by efficient transfer of central chirality into axial chirality.